Recurrent Bilateral Optic Neuritis Associated with Myelin Oligodendrocyte Glycoprotein Antibody: A Case Report from Nepal - Sangam Shah; Rajeev Ojha; Sanjeeta Sitaula; Dosti Regmi; Ragesh Karn; Bikram Prasad Gajurel; Reema Rajbhandari; Niraj Gautam; Sunanda Paudel; Aashish Shrestha (Case Reports in Neurological Medicine)
Neuromyelitis optica spectrum disorder (NMOSD) is an immune-mediated inflammatory condition involving spinal cord and optic nerves. Diagnosis of NMOSD is done by aquaporin-4 antibody (AQP4) in patients with optic neuritis. Myelin oligodendrocyte glycoprotein (MOG) expressed on the oligodendrocyte cell surface and on the outermost cell surface of the myelin sheath may also be present in patients with NMOSD bilateral optic neuritis. Here, we describe a case of a thirty-nine-year-old-female with recurrent bilateral optic neuritis with positive anti-MOG antibody, and anti-MOG syndrome has not previously been reported from Nepal.